Description of five new species of Cnemomis, with a key to the known species (Hemiptera: Heteroptera: Coreidae: Discogastrini) - Brailovsky, Harry (Zootaxa, 2015)
Five new species of the genus Cnemomis Stål, 1859 are described: C. kondratieffi from Brazil and French Guyana, C. lepida from French Guyana, C. nigroscutellata from Brazil, C. primigena from Peru, and C. refulgens from Venezuela. New distributional records for some previously known species are added. Dorsal view photographs and a key for the 13 known species are included. The male genital capsule of C. kondratieffi and C. lepida are illustrated.